Situación de la auxiliares de odontología del suroccidente colombiano egresadas de la Universidad del Valle - Pérez Flórez, Yolanda (Revista Estomatología, 1993)
The Department of Stomatology of University of Valle has been training dentists and dental auxiliary personneL It has been interested in researching the follow-up of their professional life of its alumni. The present descriptive study was carried out taking into account the auxiliary personnel population of Southwest of Colombia. These assistants were trained between July 1973 and December 1990. The questionnaires were sent out to a sample of 170 auxiliaris. From this population 139 filledout the questionnaires and when these were tallied, the asistants fell into the following categories: 44,6% (62) dental hygienists; 33,8% (47) dental assistants and 21,6% (30) "Dental nurses o fNew Zealand" but these are onlyinvolved in making restorations. The results showed that the majorityof these assistants lived in big cities of the southwest and they worked at State Dental Institutions. They rated highly their academic training at the University ofValle, and they also showed satisfaction with their present jobs and salary. From them auxiliaries who expressed satisfaction, a smal population recoggnized that this was due mainly to their low salary and just a very few ofthem blamed their unfortunate condition to their academic training. Suggestions related to academic training were also obtained. The results and suggestions obtainecl in this study will be usecl in the near future to improve the present study courses in the acaclemic training of dental auxiliary personnel at the Departament of Stomatology of the University of Valle at Cali in Colombia.